Identification of protective pneumococcal T(H)17 antigens from the soluble fraction of a killed whole cell vaccine - Kristin, L Moffitt (Public Library of Science (PLoS), 2018)
Mucosal or parenteral immunization with a killed unencapsulated pneumococcal whole cell antigen (WCA) with an adjuvant protects mice from colonization by a T(H)17 CD4+ cell-mediated mechanism. Using preparative SDS gels, we separated the soluble proteins that compose the WCA in order to identify fractions that were immunogenic and protective. We screened these fractions for their ability to stimulate IL-17A secretion from splenocytes obtained from mice immunized with WCA and adjuvant. We identified 12 proteins within the stimulatory fractions by mass spectrometry; these proteins were then cloned, recombinantly expressed and purified using an Escherichia coli expression system. The ability of these proteins to induce IL-17A secretion was then evaluated by stimulation of mouse splenocytes. Of the four most stimulatory proteins, three were protective in a mouse pneumococcal serotype 6B colonization model. This work thus describes a method for identifying immunogenic proteins from the soluble fraction of pneumococcus and shows that several of the proteins identified protect mice from colonization when used as mucosal vaccines. We propose that, by providing protection against pneumococcal colonization, one or more of these proteins may serve as components of a multivalent pneumococcal vaccine.